Pengembangan Model Kurikulum Pendidikan Agama Islam Berbasis Multikultural - Haj, Habil Syahril; Marno, Marno (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
In the context of globalization and cultural diversity, religious education needs to accommodate societal diversity to remain relevant and inclusive. This research employs a curriculum development approach to design a model that integrates Islamic values with the concept of multiculturalism, aiming to develop a Multicultural-Based Islamic Religious Education curriculum. The methodology utilized a qualitative approach through interviews, observations, and document analysis. The findings of the research emphasize the importance of a multicultural-based Islamic religious education curriculum, given that Indonesia is a diverse nation comprising various ethnicities, languages, religions, and cultures. Implementing a multicultural-based Islamic religious education curriculum is expected to have a positive impact on fostering harmony and tolerance among individuals.